Consequences and global risks of highly pathogenic avian influenza outbreaks in poultry in the United Kingdom. (April 2023) - Haider, Najmul; Kock, Richard; Zumla, Alimuddin; Lee, Shui Shan
Highlights: Ongoing HPAI outbreaks have resulted in the culling of >4.6 M birds in the UK. The outbreak could increase the risk of zoonotic transmission. Increase potential for mixing of the influenza viruses of other species. The UK faces significant disruption of chicken egg supplies in the supermarkets. Free-range chicken eggs are becoming scarce.